Kajian Sosiologi Sastra Pada Tokoh Utama Dalam Novel al-Rajul al-Ladzi Amana Karya Najib al-Kaelani - Ariyanti, Novi (Arabiyatuna : Jurnal Bahasa Arab, 2019)
This study aims to describe the form of characters and characterizations of the novel al-Rajullu al-Ladzi Amana by Najib al-Kaelani and sociology major figures. This research uses qualitative descriptive method. The results of the research there were ten characters and characterizations in the novel al-Rajullu al-Ladzi Amana they are Iryan, sophia, Syamsi, Maishun, Ayah, Ibu, Ali, Shaqr, Beneto, Syeikh Idul Husain. The sociology major figures in the novel al-Rajullu al-Ladzi Amana divided into three, namely the role of Iryan Iryan roles as individuals, as members of the family, and the role of Iryan as members of the community.